Upaya Meningkatkan Kemampuan Berbicara Melalui Penggunaan Media Flash Card Pada Anak Kelompok A TK Pertiwi I Dukuh Banyudono Boyolali Tahun Pelajaran 2014/2015 - Istiqomah, Umi, Drs. Hasto Daryanto, M.Pd, Willi Astuti, S.Pd., M.Hum (2015)
Speaking is a skill to deliver a message through spoken language. According Mulgrave speaking just not prounouncing sounds or words but talk form a tool for communicate ideas that are prepared in accordance with the needs of hearing. The use of media to practice speaking skills are still monotonous in kindergareten one of the low of speech in children. Flash media card is a media alternative media are used to enhance the ability to speak in early childhood. The purpose of this research is to improve speaking skills through the use of flash media card on A group of children TK Pertiwi I Dukuh. This type of research study with working procedure cycles consist of four stages. The research subjects were teachers and children in group A at TK Pertiwi I Dukuh Banyudono Boyolali. The results of this study indicate that the flash media card is able to improve the ability to speak. The percentage from pre action class room research to cycle II is, pre cycle 44.65%, cycle I 62.10% and cycle III 82.15%. Conclusions of this study the increased ability to speak through the use of flash media card on A group of children kindergarten Pertiwi I Dukuh in the academic year of 2014 / 2015. keywords : speech , flash media card